Fluorotelomer alcohols (FTOHs), brominated flame retardants (BFRs), organophosphorus flame retardants (OPFRs) and cyclic volatile methylsiloxanes (cVMSs) in indoor air from occupational and home environments. (October 2018) - Sha, Bo; Dahlberg, Anna-Karin; Wiberg, Karin; Ahrens, Lutz
Abstract: Indoor air samples were collected from private homes and various occupational indoor environments using passive air sampler and analysed for fluorotelomer alcohols (FTOHs), brominated flame retardants (BFRs), organophosphorus flame retardants (OPFRs) and cyclic volatile methyl siloxanes (cVMSs). The aim was to investigate their occurrence in indoor air, factors that may affect their presence and human daily exposure dose (DED) via inhalation. In general, levels of cVMSs were 3–4 orders of magnitude greater than the other compound classes. OPFRs concentration was found significantly higher than BFRs in indoor air. The most abundant compounds in each chemical class were 8:2 FTOH, 2, 4, 6-TBP, TNBP and TCEP and decamethylcyclopentasiloxane (D5). Home samples contained higher level of FTOHs, BFRs and cVMSs than occupational environments, whereas concentration of OPFRs in office samples were higher. BFRs concentrations were significantly correlated with building age and with the number of electronic/electrical devices at the sampling sites. Moreover, significantly lower levels of FTOHs and cVMSs were observed in rooms with forced-ventilation system. Estimated DED via inhalation was significantly higher at home than in office and the total DED was on average 3–5 orders of magnitude lower than the reference value. Graphical abstract: Highlights: PFASs, BFRs, OPFRs and cVMSs present in residential and occupational indoor air. Building ages and brominated flame retardant levels were positively correlated. Ventilation conditions may have an influence on the presence of indoor contaminants. Estimation of human exposure via inhalation to four emerging contaminant classes. Abstract : To close the knowledge gap of emerging pollutants in indoor air in occupational and home environments, this study examined the presence of four different categories of emerging pollutants in various indoor environments using passive sampling, to investigate factors that affect their occurrence and estimate human exposure via inhalation.